2014
DOI: 10.5114/kitp.2014.45676
|View full text |Cite
|
Sign up to set email alerts
|

THORACIC SURGERY Genetic basis of keloid formation in wounds after cardiac surgery

Abstract: Keloid disease is the abnormal formation of scar tissue in genetically predisposed people. Among many genes which may be related to the development of keloids, transforming growth factor β1 (TGF-β1) is one of the most mentioned. It encodes cytokinin, which is responsible for the production of extracellular matrix and takes part in healing. Any abnormalities which arise during synthesis of the protein as a result of polymorphism or gene mutation may be the cause of healing disorders (scarring of the body); thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“… 27 , 30 One study was a nested case–control design 28 (all cases were identified from a cohort and matched controls selected from the same cohort) and the fourth used a case–control design. 29 Two studies focused on the role of genetic variation in the development of hypertrophic scarring, 28 , 30 one of keloid scarring, 29 and one of both hypertrophic and keloid scarring (although no cases of keloid scarring were detected). 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 , 30 One study was a nested case–control design 28 (all cases were identified from a cohort and matched controls selected from the same cohort) and the fourth used a case–control design. 29 Two studies focused on the role of genetic variation in the development of hypertrophic scarring, 28 , 30 one of keloid scarring, 29 and one of both hypertrophic and keloid scarring (although no cases of keloid scarring were detected). 27 …”
Section: Resultsmentioning
confidence: 99%
“…Participants in all four acute surgical wound studies were ≥18 years. Surgery was cesarean section ( n = 2), 27 , 28 cardiac surgery ( n = 1), 29 and melanoma excision ( n = 1). 30 One study excluded people with recorded histories of pathological scar formation or benign or malignant tumors 27 and one excluded patients whose incision overlapped with previous surgeries or trauma.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 564 keloid cases and 620 healthy controls were included in the five case-control studies. 10 , 12 – 15 The publishing years ranged from 2003 to 2015. Two of the five studies were conducted in Chinese populations and the remaining three studies were conducted in Caucasian, Malay and Polish populations, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…CT or TT genotype) of TGF-β1 -509C/T was related to a significantly lower risk of KD in a Polish population (OR = 0.321, 95% CI = 0.119–0.870, P = 0.03). 13 There were two studies on the relationship between the TGF-β1 -509C/T polymorphism and susceptibility to KD in a Chinese population. Song et al found that Chinese individuals with allele C (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation